1986
DOI: 10.1016/0011-9164(86)85001-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer, fluid flow and membrane properties in flat and corrugated plate hyperfiltration modules

Abstract: SUMMARYConcentration polarisation, decreasing the efficiency in membrane separation processes, can be reduced by increasing mass transfer between membrane surface and bulk of the feed stream. Analogous to techniques used in plate heat exchangers efforts have been made to enhance mass transfer in a plate hyperfiltration module by using a corrugated membrane in stead of a flat one. The corrugations are pressed into an originally flat membrane. These corrugations do not only have an influence on the mass transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Various other techniques such as pulsatile and reverse flow [11], vortex generators [12], corrugated membrane surface [13] and pretreatment of membrane surface [14] to prevent fouling have been used to enhance the permeate flux. The principal limitation to wider application of this technique is in the flux decline associated with concentration polarization and fouling of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various other techniques such as pulsatile and reverse flow [11], vortex generators [12], corrugated membrane surface [13] and pretreatment of membrane surface [14] to prevent fouling have been used to enhance the permeate flux. The principal limitation to wider application of this technique is in the flux decline associated with concentration polarization and fouling of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was observed experimentally that baffles placed on the membrane are effective in enhancing mass transfer by producing the vortices (Racz et al, 1986;Colman and Mitchell, 1990), few theoretical works have been reported in the literature. The purpose of this work is to investigate numerically the effect on CP of the turbulent flow with vortices induced by baffles of rectangular or triangular shapes.…”
Section: Membrane Modulementioning
confidence: 96%
“…Placing protuberances or corrugations directly onto the membrane surface has an influence on the mass transfer. Corrugations enhance mass transfer in more effective way than an increase in flow rate does (Racz et al, 1986). Colman and Mitchell (1990) investigated vortex mixing generated by pulsed flow to improve membrane performance.…”
Section: Membrane Modulementioning
confidence: 98%
“…In order to further increase efficiency while maintaining a stable operational performance, the control of concentration polarization and subsequent membrane fouling is of great importance [5]. Techniques shown to be effective include turbulence promoters [6,7], corrugated membrane surfaces [8], pulsatile flow [9] and vortex generation [10,11]. However, Bellara et al [12] demonstrated that injecting air bubble is a cheap and effective way of reducing concentration polarization and thus enhancing the permeate flux in hollow fiber membrane modules.…”
Section: Introductionmentioning
confidence: 97%